Chomskyan Theory and Cognition Study Linguistic Cognitive Interdisciplinary approach - Rajeh, Ibrahim Mohamed Ali (Arab Journal for Sciences and Research Publishing, 2019)
Underpinned by contemporary epistemology in conjunction with cognitive science, cognitive psychology and cognitive neuroscience, this interdisciplinary linguistic study titled “Chomskyan Theory and Cognition Study” aims to examine and explain how can Chomskyan Linguistics contributes to understanding of epistemological issues (cognition/mental process) in accordance with his hypothesis’s question: What contribution can the study of language make to our understanding of human nature? To investigate the achievability of Chomsky theory in tackling such issues, this study utilizes essentially the interdisciplinary analytical linguistic method in cooperation with other methods. Eventually, the study has come to multiple findings, most significantly that study of language according to CL not only contributes to understanding of human intelligence and nature; but it is utterly intrinsic in this matter and it provides a great understanding of how we can decode the puzzle of consciousness and its phenomena via explaining the universal principles of human language.